Neuro-imaging in dementia: using MRI in routine work-up - Scheltens, Philip (Henry Stewart Talks, 2007)
Changing role of structural imaging in dementia, Current diagnostic use, Sensitivity and specificity, Identifying biological markers for disease, Examples from clinical practice
Archived at 2020/08/13